2010
DOI: 10.1177/039156031007700307
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Therapeutic Approach in Patients with Urinary Calculi

Abstract: The natural history of urolithiasis includes the risk of recurrence and of the development of chronic kidney and/or bone disease, which is why a thorough clinical and metabolic evaluation of these patients is of the utmost importance at disease onset. This paper is aimed at identifying the type of urolithiasis, the related risk factors, and the corresponding treatment options. The diagnostic and therapeutic approach described here includes 1) accurate history taking to detect secondary nephrolithiasis and scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…In regard to imaging, experts were more inclined to recommend unenhanced low-dose abdominal CT, although ultrasound -KUB X-ray seems an acceptable alternative. This is in accordance with most of the existing guidelines, [9][10][11][12][13] probably because CT can eliminate most of the alternative diagnoses and shows better diagnostic performances. [17] However, in a recent large multicentre randomized trial, Smith-Bindman et al found that initial ultrasonography for suspected renal colic was associated with lower cumulative radiation exposure than initial CT without significant differences in missing high-risk diagnoses, which emphasizes that controversies regarding this question are still ongoing.…”
Section: Diagnostic Approachsupporting
confidence: 89%
See 1 more Smart Citation
“…In regard to imaging, experts were more inclined to recommend unenhanced low-dose abdominal CT, although ultrasound -KUB X-ray seems an acceptable alternative. This is in accordance with most of the existing guidelines, [9][10][11][12][13] probably because CT can eliminate most of the alternative diagnoses and shows better diagnostic performances. [17] However, in a recent large multicentre randomized trial, Smith-Bindman et al found that initial ultrasonography for suspected renal colic was associated with lower cumulative radiation exposure than initial CT without significant differences in missing high-risk diagnoses, which emphasizes that controversies regarding this question are still ongoing.…”
Section: Diagnostic Approachsupporting
confidence: 89%
“…[8] Guidelines for the management of urinary stone disease in the hospital setting have been made by urologists, [9] emergency physicians [10] and radiologists, [11] but there is a lack of recommendations for management in primary care. [12,13] The aim of this study was to generate proposals for the management of urolithiasis in general practice in France, using a Delphi method.…”
Section: Introductionmentioning
confidence: 99%
“…There is still much debate on whether a single collection be adequate, if spot urine could substitute for 24-hour urine, if complete evaluation should be only offered to recurrent stone formers or even to patients at first episode. These issues are discussed in referenced papers (23,71,72). The author's opinion is that one 24-hr urine collection associated with fasting urine collection could be a reasonable option to be offered to recurrent stone formers or even single stone formers with risk conditions such as systemic disorders, family history, early onset, renal insufficiency, etc.…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…4,5 Some guidelines recommend a sonogram and an abdominal radiography as first diagnostic imaging investigations. 6,7 The sonogram has several advantageous features: fast, accurate execution at the bedside, at low cost, and allows for ruling out other possible causes of abdominal pain. A meta-analysis, aggregating five high-quality studies, found a modest overall accuracy, for sonography, in diagnosing nephrolithiasis: sensitivity of 70% and a specificity of 75%.…”
mentioning
confidence: 99%